Language Tools for Creating Image in Online Advertising (On the Material of Sites of Slavic cuisine Restaurants) - Sknarev, Dmitry; Mahmoud Agha, Munir (International Journal of Psychosocial Rehabilitation, 2020)
Advertising a restaurant on the Internet is the most effective way to declare your business, based on high competition and the struggle for uniqueness and recognition. The relevance of the study is due to the problem of creating an advertising image in Internet communication. The study is aimed at studying the language of creating an image in Internet advertising (on the example of sites of Slavic cuisine restaurants) and at analyzing the verbal image of a restaurant in Internet advertising in a collaboration, from the point of view of marketing and philology, within the framework of the existing new direction of modern science—linguistic marketing. The study makes a significant contribution to the development of linguistic marketing and offers new theoretical approaches to the discursive analysis of language units. In the framework of this study, the cuisine of the eastern (Russian, Ukrainian, Belarusian), southern (Bulgarian, Serbian), and western (Polish, Czech) Slavs was considered. The material was web media texts—sites of Slavic cuisine restaurants in Moscow, more than 100 texts of online advertising in all. To achieve the goal of the study, various methods and techniques were used: analytical, theoretical, and systemic methods; quantitative methods; continuous selection of the language means of marketing communications units that create an image of a product from online advertising texts; and the quantitatively symptomatic part of linguistic and statistical methods. The authors of the article define the figurativeness of speech as one of the most powerful means of influence in Internet advertising. The study found that among the language means of creating an advertising image of a Slavic cuisine restaurant, brand names, epithets, comparisons, metaphors, and phraseological units are the most productive. These language tools form the image of the Slavic cuisine restaurant, characterizing its specificity, atmosphere, location, interior, furniture, quality of products, dishes and their preparation, prices, national flavor, etc. The study substantiates that the image presented in the advertising communication of the Slavic cuisine restaurant may suggest its national flavor and high-quality products, increasing its attractiveness to the consumer and giving it additional consumer value. The materials of the study are of practical value for students of humanitarian specialties and areas, for specialists in the field of advertising, as well as for all those who love and study modern advertising.